Early Childhood Creativity Festival Super Kids for a Great Indonesia: Through Batik Fashion Show, Puzzle Competition, and National Song Singing Competition at the North Sumatra State Museum - Putri Sari Ulfa Sembiring; Azizah Muthmainnah; Puri Telembanua (Outline Journal of Community Development, 2026)
The Community Service Program entitled "Early Childhood Creativity Festival: Super Kids for a Great Indonesia" aimed to enhance young children's creativity, self-confidence, critical thinking skills, and appreciation of Indonesian culture and national values. The program was conducted at the North Sumatra State Museum and involved children from several Early Childhood Education (ECE) institutions. The implementation consisted of three stages: preparation, implementation, and evaluation. The activities included a batik fashion competition, a puzzle competition, and a national song singing competition, followed by an educational museum tour. Evaluation was carried out through direct observation of children's participation, enthusiasm, and performance throughout the activities. The results indicated that the participants actively engaged in all activities and demonstrated improved confidence, creativity, logical thinking skills, and awareness of Indonesian cultural heritage and nationalism. Furthermore, the program strengthened collaboration among the university, ECE institutions, parents, and museum management in creating an educational, enjoyable, and character-building learning environment for young children.